1998
DOI: 10.1161/01.res.83.9.877
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Sarcolemmal Calcium Pump in the Myocardium of Transgenic Rats

Abstract: Abstract-The plasma membrane calmodulin-dependent calcium ATPase (PMCA) is a calcium-extruding enzyme controlling Ca 2ϩ homeostasis in nonexcitable cells. However, its function in the myocardium is unclear because of the presence of the Na ϩ /Ca 2ϩ exchanger. We approached the question of the physiological function of the calcium pump using a transgenic "gain of function" model. Transgenic rat lines carrying the human PMCA 4 cDNA under control of the ventricle-specific myosin light chain-2 promoter were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 64 publications
3
80
0
1
Order By: Relevance
“…Due to their widespread distribution, they are thought to be important "housekeeping" Ca 2+ -pumps, but their function in smooth muscle is less well known. In addition to Ca 2+ homeostasis, it has been suggested that PMCA is associated with vascular smooth muscle proliferation (Abramowitz et al, 2000) and signal transduction (Hammes et al, 1998). The latter is based on the PDZ domains in PMCA4b which lead to a complex with nitric oxide synthase I in caveolae of vascular smooth muscle (Schuh et al, 2001).…”
Section: Plasma Membrane Ca 2+ Pumpsmentioning
confidence: 99%
“…Due to their widespread distribution, they are thought to be important "housekeeping" Ca 2+ -pumps, but their function in smooth muscle is less well known. In addition to Ca 2+ homeostasis, it has been suggested that PMCA is associated with vascular smooth muscle proliferation (Abramowitz et al, 2000) and signal transduction (Hammes et al, 1998). The latter is based on the PDZ domains in PMCA4b which lead to a complex with nitric oxide synthase I in caveolae of vascular smooth muscle (Schuh et al, 2001).…”
Section: Plasma Membrane Ca 2+ Pumpsmentioning
confidence: 99%
“…Further processing was according to standard procedures. 7 Protein was visualized with the ECL detection system (Amersham Pharmacia Biotech). Signals were quantified with ScanPack (Biometra).…”
Section: Calcineurin Protein Expressionmentioning
confidence: 99%
“…Recently, a role of the carboxyeosin-sensitive Ca 2ϩ -ATPase PMCA in controlling resting [Ca 2ϩ ] i and the reduction in [Ca 2ϩ ] i after an increase in [Ca 2ϩ ] i in rat ventricular myocytes has been demonstrated (12). In contrast to these observations, overexpression of PMCA4b in the myocardium of transgenic rats did not result in an altered regulation of contraction/relaxation cycle but in an enhanced growth response of cardiac myocytes to different stimuli (13). Additionally, it has been shown that the C termini of several PMCA variants, especially variants PMCA4b and PMCA2b, bind to PDZ domains of proteins of the MAGUK (membrane-associated guanylate kinases) family (14,15), to the PDZ domain of nitricoxide synthase I (nNOS, NOS-I (16)) and to Na ϩ /H ϩ exchanger regulatory factor (NHERF (23)).…”
mentioning
confidence: 96%